Impacto do tratamento com terapias educacionais e de autocuidados no padrão cinesiográfico mandibular e no desempenho mastigatório de mulheres com disfunção temporomandibular crônica dolorosa - Giro, Gabriela [UNESP] (2015)
The temporomandibular disorders (TMD) may cause functional limitations, such as restrictions of mandibular movements, and reduced capacity masticatory. The aim of this study was to investigate the impact of treatment with educational about TMD and self-care therapies on the mandibular movement pattern and masticatory performance of chronic painful TMD women. Fifty-two women diagnosed with TMD according to the Research Diagnostic Criteria for Temporomandibular Disorders (RDC / TMD) Axis I and II - Portuguese version, were selected and randomly divided into 3 groups: control (CG, n=16), education group (EG, n=18), and education and self-care (ESG, n=18), according to the treatment sequence that they received. A kinesiograph device recorded mandibular movements during maximum mouth opening and chewing, and the masticatory performance was evaluated by the sieves method. These analyzes were performed at baseline (T0), after 30 (T1) and 60 (T2) days of follow-up. The paired sample t-test was used to compare the data obtained at T0 and T1, for each group (α = 0.05). Moreover, a comparison among the groups in each moment, was performed using the parametric test 1-way ANOVA, followed by Bonferroni test for multiple comparisons of means (α=0.05). Regarding to kinesiographic records, similar results were found at T0 compared with T1, for the CG and EG groups. Already, the ESG group showed a significant increase in vertical (T0=30.5±6.0mm; T1=35.6±6.4mm (p=0.000)) and anteroposterior (T0=18.1±8.9mm; T1=25.6±9.5mm (p=0.016)) mandibular movements during maximum mouth opening, and an increase in the vertical mandibular movement (T0=16±1.4mm; T1=1.7mm±17.4 (p=0.023)) during chewing, after 30 days of follow-up. Considering the masticatory performance, no significant differences were found between the periods (T0-T1), for all groups. In addition, after 30 and 60 days of follow-up...(Complete abstract electronic access below)